2019
DOI: 10.1093/europace/euz183
|View full text |Cite
|
Sign up to set email alerts
|

Association between pre-ablation bariatric surgery and atrial fibrillation recurrence in morbidly obese patients undergoing atrial fibrillation ablation

Abstract: Aims Obesity decreases arrhythmia-free survival after atrial fibrillation (AF) ablation by mechanisms that are not fully understood. We investigated the impact of pre-ablation bariatric surgery (BS) on AF recurrence after ablation. Methods and results In this retrospective observational cohort study, 239 consecutive morbidly obese patients (body mass index ≥40 kg/m2 or ≥35 kg/m2 with obesity-related complications) were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 25 publications
2
52
0
1
Order By: Relevance
“…This raises the possibility that prolonged morbid obesity or long-standing persistent AF (or both) may portend an irreversible substrate—‘too little too late’. However, a recent report of managing morbid obesity and predominantly patients with persistent AF using bariatric surgery has challenged this notion demonstrating significant improvement in maintenance of sinus rhythm after ablation 50…”
Section: Additional Studies Addressing Risk Factors For Afmentioning
confidence: 99%
“…This raises the possibility that prolonged morbid obesity or long-standing persistent AF (or both) may portend an irreversible substrate—‘too little too late’. However, a recent report of managing morbid obesity and predominantly patients with persistent AF using bariatric surgery has challenged this notion demonstrating significant improvement in maintenance of sinus rhythm after ablation 50…”
Section: Additional Studies Addressing Risk Factors For Afmentioning
confidence: 99%
“…The literature extensively describes that poorly controlled obesity and diabetes lead to increased AF recurrence rates after catheter ablation [13][14][15] . Risk factor modi cation like weight loss with or without bariatric surgery, glycemic control, blood pressure control, and sleep apnea treatment have been shown to increase arrhythmia-free survival rates 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus (DM) also is a risk factor, presumably due to increased left ventricular mass and arterial stiffness 12 . Studies have shown that obesity and diabetes, particularly when poorly managed, are associated with high rates of AF recurrence after ablation [13][14][15] . Others have shown that risk factor modi cation reduces the risk of incident and recurrent AF 16,17 .…”
mentioning
confidence: 99%
“…Unfortunately, research has shown that this strategy is anything but simple: virtually, no adults (<1%) are compliant with all recommendations and 42% are compliant with only 0-2 recommendations (Folsom et al, 2011). Although there is ample evidence that weight loss and maintaining an ideal weight are beneficial in reducing AF burden and symptoms, compliance with this recommendation is poor; the reasons include among others, inability to track food intake (Abed et al, 2013, Donnellan et al, 2019.…”
Section: Dietmentioning
confidence: 99%